The influence of public health organization on response to the COVID-19 pandemic in four Canadian provinces: A comparative qualitative analysis - Susan Usher; Sara Allin; Lara Gautier; Katherine Fierlbeck; Veena Sriram; Aidan Bodner; Camille Trapé; Leah Shipton; Alessia Montecalvo; Peter Berman (Health Policy Open, 2025)
Background: Studies of COVID-19 pandemic responses reveal shortcomings that may relate to the organization of public health systems. Objective: This study uncovers the organizational factors that may strengthen pandemic responses in high-income countries through a comparative analysis of four Canadian provinces. Methods: We undertook a qualitative multiple case study, collecting data through document review and 103 interviews with government and non-governmental actors involved in pandemic response. Analysis explored how differences in the organization of provincial public health systems influenced decision-making, advisory, coordination and adaptation processes. Results: The scale of the pandemic positioned the Premier as legitimate decision-maker in all provinces regardless of the distribution of authority in their public health systems. Capacity for generating public health advice was increased through existing or new organizations and highlighted the advantage of links to university expertise. All public health systems relied on healthcare resources for testing programs despite differences in the integration of public health under healthcare governance structures; centralization of healthcare governance was a facilitator. Adapting pandemic control measures to population needs was supported by linkages between organizations capable of apprehending needs and organizations that made decisions. Conclusions: This study builds on the literature of pandemic responses across high-income countries and uncovers organizational factors that may enhance agility to rapidly expand capacities, connect actors for emergency responses, and strengthen public health systems.